Bioclimate-based species distribution modelling of the two key insect pests of Theobroma cacao in the Philippines - Navarrosa, Tisha Marie F. (Animo Repository, 2021)
Theobroma cacao (Malvaceae) or cacao is an economically significant plant which serves as a crucial source of food production grown in the humid tropics as a plantation crop. The pest species that greatly affect the production of cacao in the Philippines are Helopeltis bakeri and Conopomorpha cramerella, whose recent emergence has been affecting plantations nationwide. The main objective of this study is to model the distribution of H. bakeri and C. cramerella based on bioclimatic variables using the Maxent algorithm. Pre-existing survey points of the two species were used for model training and testing. The AUC values for the models generated were close to 1.0, indicating that the models’ for H. bakeri and C. cramerella have high predictive power. The response curves generated by the Maxent model were able to identify which bioclimatic variables are responsive to the two species. The probable areas were verified using presence data obtained from cacao farmers who encountered the species. These farmers were reached out to using Facebook, with the locations estimated and photos used with their consent. The bioclimatic variable found to have the highest percent contribution for H. bakeri was the mean temperature of the warmest quarter (bio10) which has the value of 85.5%, while for C. cramerella the bioclimatic variable that have highest percentage contribution was the mean diurnal range (bio02) which has the value of 81.3%